Proposed new signal for real-time stress monitoring: Combination of physiological measures - M. Saidi; H. Hassanpoor; A. Azizi Lari (AUT Journal of Electrical Engineering)
Human stress is a physiological tension that appears when a person responds to mental, emotional, or physical chal-lenges. Detecting human stress and developing methods to manage it, has become an important issue nowadays. Au-tomatic stress detection through physiological signals may be a useful method for solving this problem. In most of the earlier studies, long-term time window was considered for stress detection. Continues and real-time representation of the stress level is usually done through one physiological signal. In this paper, a real-time stress monitoring system is pro-posed which shows the user a new signal for feedback stress level. This signal is combined of weighted features of gal-vanic skin response and photoplethysmography signals. The features are defined in 20-sec time windows. Correlation feature selection and linear regression methods are used for feature selection and feature combination respectively. Furthermore, a set of experiments was conducted for training and testing of the proposed model. The proposed model can represent the relative stress level perfectly and has 79% accuracy for classifying the stress and relaxation phases into two categories by a determined threshold.